Comparison of Different Rotary Nickel–titanium Systems to Evaluate Coronal Leakage of Root Canals: An in Vitro Study - Rasha M Al-Shamaa (Dental Hypotheses, 2023)
Introduction: The objective of the study was to assess coronal leakage following root canal treatment utilizing four Micro Mega rotary nickel–titanium files, specifically One shape, Two shape (s1), Two shape (s2), and Revo-S, by means of dye penetration analysis using a stereomicroscope set at 20× magnification. Methods: Fifty human lower premolar teeth that were extracted for orthodontic reasons were included in the study, excluding teeth with cracks, caries, severe curvature (<25°), or root resorption. The teeth were randomly assigned to five groups using www.random.org www.random.org, and standard endodontic treatments were performed as per the manufacturer’s instructions using Micro Mega One shape, Two shape (s1), Two shape (s2), and Revo-S rotary nickel–titanium systems. To measure dye penetration, the teeth were immersed in a 2% methylene blue dye solution for approximately 24 hours and then axially split using a diamond sectioning disc, with measurements taken using a stereomicroscope. Results: The study groups showed statistically significant differences (P < 0.001), and all pairwise comparisons were found to be significantly different according to the post hoc test (P < 0.001). Conclusion: Our results showed that various rotary file designs significantly affect coronal leakage.